Thermo-sensitive hydrogel dressing loaded with trypsin antibacterial biofilm as well as preparation method and application of thermo-sensitive hydrogel dressing
Through the thermosensitive quaternary ammonium chitosan hydrogel loaded with trypsin, the problem of removing bacterial biofilm in chronic wounds is solved, and efficient and safe wound healing is achieved, suitable for irregular wounds and reduces costs.
Patent Information
- Application Number
- CN202411722238.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively solve the removal of bacterial biofilms in chronic wounds, resulting in the hindrance of the healing process. Traditional hydrogel dressings have difficulties in taking into account both antibacterial and biosafety, are not suitable for deep or irregular wounds, and are cost-effective.
Trypsin-loaded thermosensitive quaternary ammonium chitosan hydrogel is used to form a hydrogel dressing with high antibacterial properties and good biosafety through physical crosslinking of α, β-glycerol phosphate and chemical crosslinking of jinipin.
This hydrogel dressing can effectively destroy bacterial biofilms, promote the healing of chronic wounds, and has high efficiency antibacterial properties and good biosafety. It is suitable for irregular wounds and reduces production costs.
Smart Images

Figure CN119499437A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a temperature-sensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, and a preparation method and application thereof. Background Art
[0002] With the aging of the population, the incidence of chronic wounds such as diabetic foot ulcers, pressure ulcers and vascular ulcers has gradually increased. It is reported that the treatment and care of chronic wounds accounts for at least 5.5% of the total medical expenditure in developed countries. 85% of amputations worldwide are related to ulcers, and the 5-year mortality rate after amputation is between 40% and 70%, and it is even higher in major amputation cases, resulting in a huge socioeconomic burden and seriously affecting the quality of life of patients and their families. The main reason for the failure of trauma treatment is repeated and persistent bacterial infection. Bacterial biofilm formation can be detected in at least 80% of chronic wounds. Bacterial biofilm is a microenvironment where bacteria aggregate and a self-secreted extracellular polymer matrix (EPS), which includes: extracellular DNA, proteins, polysaccharides and other substances. The formation of bacterial biofilm in chronic wounds involves complex and dynamic interactions between the wound, microorganisms and EPS, which makes it extremely difficult to remove bacterial biofilms, which in turn seriously hinders the healing process of chronic wounds.
[0003] According to the diagnostic and treatment guidelines of the European Association of Clinical Microbiology and Infectious Diseases, for patients with chronic wounds with bacterial biofilm formation, it is recommended to perform extended wound debridement and empirically use local or systemic antibiotics to control infection. However, under naked eye observation, it is impossible to determine whether EPS can be completely removed by debridement, and local use of antibiotics is prone to antibiotic resistance, while systemic use of antibiotics is not effective in controlling wound infection. Currently, some researchers use antimicrobial peptides (AMPs) to target bacterial biofilm formation in chronic wounds. However, the metabolic instability of AMPs limits their clinical application. Some studies use bacteriophages to destroy bacterial biofilms, but the high specificity of bacteriophages limits their application in diseases with mixed bacterial biofilm formation. Bacterial biofilm-degrading enzymes can effectively destroy EPS, such as staphylococcal serine proteases, staphylococcal proteases, and staphylococcal serine proteases. However, free bacteria may lead to new biofilms again. Therefore, there is a need for an efficient broad-spectrum antibacterial agent that can simultaneously destroy EPS and the bacteria encapsulated therein.
[0004] Hydrogel dressings are a type of gel-like material that contains a large amount of water, usually made by combining water molecules with polymer materials (such as gelatin, hydroxyethyl cellulose, etc.). They are widely used in the treatment and postoperative care of burn wounds, chronic ulcer wounds, etc. The possible problems and their potential causes are as follows:
[0005] 1) High efficiency, ultra-broad-spectrum antibacterial properties and biosafety cannot be achieved at the same time. Since topical use of antibiotics is prone to drug resistance, hydrogel dressings basically achieve antibacterial properties by adding silver ions. However, long-term use of silver ions on chronic wounds will lead to accumulation of heavy metals, which are toxic to the human body.
[0006] 2) Not suitable for chronic wounds of irregular depth and shape;
[0007] 3) The opacity of the dressing prevents medical staff from directly observing the wound condition, which may hinder timely monitoring and evaluation;
[0008] 4) The use of materials such as gelatin and hydroxyethyl cellulose and the complex preparation process lead to high dressing costs, limiting their widespread application;
[0009] 5) Mechanical strength and flexibility cannot be taken into account at the same time.
[0010] Therefore, how to provide a hydrogel dressing to solve the technical problems in the prior art that infectious wounds are difficult to treat and that patients have poor recovery in the later stages is an issue that needs to be urgently addressed by those skilled in the art. Summary of the invention
[0011] The object of the present invention is to provide a new method for treating chronic wounds combined with bacterial biofilm formation, namely, a thermosensitive quaternary ammonium chitosan hydrogel loaded with trypsin. We use α, β-sodium glycerophosphate and quaternary ammonium chitosan (QCS) for physical crosslinking to give the hydrogel thermosensitivity. On the one hand, the change in the gel structure promotes the release of trypsin; on the other hand, the gel can be formed according to the irregular shape of the chronic wound surface to completely cover the wound surface. In addition, we introduced genipin to chemically crosslink with QCS to enhance the mechanical properties of the hydrogel. Trypsin destroys EPS by hydrolyzing extracellular proteins, and QCS has high efficiency, ultra-broad-spectrum antibacterial properties and excellent biosafety. Effectively control the formation of bacterial biofilm on the wound surface and promote the healing of chronic wounds.
[0012] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0013] The present invention provides a method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, comprising the following steps:
[0014] (1) mixing quaternary ammonium salt chitosan and trypsin to obtain a mixed solution;
[0015] (2) The mixed solution is mixed with α, β-sodium glycerophosphate for physical cross-linking, and then genipin is added for chemical cross-linking to obtain a thermosensitive hydrogel dressing loaded with trypsin antibacterial biofilm.
[0016] Preferably, the preparation method of the quaternary ammonium salt chitosan is: mixing the chitosan solution with the 2,3-epoxypropyltrimethylammonium chloride solution for 20 to 28 hours, adjusting the pH to 6.8 to 7.2, and obtaining the quaternary ammonium salt chitosan after suspension evaporation and freeze drying.
[0017] Preferably, the mass percentage concentration of the chitosan solution is 1.5-2.5%; the chitosan solution uses an alkali-urea aqueous solution as a solvent.
[0018] Preferably, the concentration of potassium hydroxide in the alkali-urea aqueous solution is 14-18 g / 100 mL, and the concentration of urea is 6-10 g / 100 mL.
[0019] Preferably, the mass percentage concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 9 to 13%.
[0020] Preferably, the volume ratio of the chitosan solution to the 2,3-epoxypropyltrimethylammonium chloride solution is 1:0.8-1.2.
[0021] Preferably, the mass ratio of the quaternary ammonium salt chitosan to trypsin is 3 to 5:1.
[0022] Preferably, the mass ratio of the mixed solution to α, β-sodium glycerophosphate and quaternary ammonium salt chitosan is 7:20-32; the mass ratio of genipin to quaternary ammonium salt chitosan is 0.01-0.03:7.
[0023] Preferably, the physical cross-linking time is 3 to 5 minutes, and the temperature is 35 to 40°C; the chemical cross-linking time is 3 to 24 hours, and the temperature is 4 to 37°C.
[0024] The invention also provides a temperature-sensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, which is prepared by the preparation method.
[0025] The present invention also provides the use of the thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm in the preparation of a product promoting wound repair.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1) It has both high efficiency, ultra-broad-spectrum antibacterial properties and good biosafety. It uses chitosan, the only alkaline polysaccharide with positive charge in nature and natural antibacterial properties, as raw material. Since it comes from organisms, it has excellent biosafety;
[0028] 2) This product adds sodium glycerophosphate to achieve a hydrogel state that changes with temperature, and its physical form changes. It is liquid at 4°C and solid at 37°C, and can completely fit the wound surface;
[0029] 3) This product is transparent dark green, and the doctor can directly observe the wound surface. At the same time, the dark green covers the bright red of the wound surface, which can improve patient acceptance;
[0030] 4) Chitosan is second only to cellulose in terms of its abundance in nature, is cheap and easy to obtain, and the present invention uses an advanced low-temperature, alkali / urea system to prepare the QCS solution, which simplifies the production steps, reduces production costs, and reduces environmental pollution;
[0031] 5) This product improves the mechanical strength of the hydrogel by adding genipin, with the tensile strength reaching 200KPa and the compressive strength reaching 8KPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0033] Figure 1 This is a photo of the thermosensitive quaternary ammonium chitosan hydrogel prepared in Example.
[0034] Figure 2 Rheological test diagram of thermosensitive quaternary ammonium salt chitosan hydrogel; it is liquid at 4°C and solid at 37°C.
[0035] Figure 3 Tensile test of temperature-sensitive quaternary ammonium chitosan (QGG) hydrogel; it can be seen that the tensile strength can reach 200KPa.
[0036] Figure 4 The trypsin release curve of the thermosensitive quaternary ammonium salt chitosan hydrogel shows that trypsin can be effectively released in a short time.
[0037] Figure 5 Crystal violet staining experiment of trypsin against bacterial biofilm in vitro (a. In vitro Staphylococcus aureus biofilm model; b. In vitro Pseudomonas aeruginosa biofilm model; the Control group used PBS solution, the QCS group used quaternary ammonium chitosan solution, the Trypsin group used trypsin solution with an enzyme activity of 0.25%, and the concentrations of the antibiotic group, QCS group and trypsin group were all 1%).
[0038] Figure 6Crystal violet staining experiment of trypsin-loaded thermosensitive quaternary ammonium chitosan (T-QGG) hydrogel against bacterial biofilm in vitro (a. in vitro Staphylococcus aureus biofilm model; b. in vitro Pseudomonas aeruginosa biofilm model; c. in vitro methicillin-resistant Staphylococcus aureus biofilm model; d. in vitro multi-durable Pseudomonas aeruginosa biofilm model; the Control group used PBS solution, the QGG group used thermosensitive quaternary ammonium chitosan hydrogel, and the T-QGG group used trypsin-loaded thermosensitive quaternary ammonium chitosan hydrogel, and the trypsin loading concentration was 1% of the total weight of the hydrogel).
[0039] Figure 7 This is a picture of the application of hydrogel in the diabetic chronic wound model.
[0040] Figure 8 The figure is a healing trend diagram of chronic wounds of diabetes with bacterial biofilm formation (the Control group used gauze, the Ag group used commercial Ag gel (Anxin Biotechnology Co., Ltd.), the QGG group used thermosensitive quaternary ammonium salt chitosan hydrogel (relative to Example 1, only trypsin was not added), and the T-QGG group used quaternary ammonium salt chitosan hydrogel loaded with trypsin). It can be seen that the use effect of T-QGG is the best, and the wounds are almost completely healed, followed by the QGG group and the commercial Ag gel group.
[0041] Fig. 9 This is a statistical chart of the healing area of chronic diabetic wounds with bacterial biofilm formation (the Control group used gauze, the Ag group used commercial Ag gel, the QGG group used thermosensitive quaternary ammonium chitosan hydrogel, and the T-QGG group used quaternary ammonium chitosan hydrogel loaded with trypsin). It can be seen that the wound healing speed in the T-QGG group was the fastest, and it was completely healed in 14 days.
[0042] Fig.10 CD31 and α-SMA immunohistochemical staining (a) and the number of new blood vessels in the wound of rats with diabetic chronic wounds accompanied by bacterial biofilm formation (b), with arrows indicating new blood vessels (the Control group used gauze, the Ag group used commercial Ag gel, the QGG group used thermosensitive quaternary ammonium chitosan hydrogel, and the T-QGG group used quaternary ammonium chitosan hydrogel loaded with trypsin). It can be seen that α-SMA and CD 31 were highly expressed in vascular smooth muscle cells and vascular endothelial cells in the T-QGG group, and the number of new blood vessels was the largest. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, comprising the following steps:
[0044] (1) mixing quaternary ammonium salt chitosan and trypsin to obtain a mixed solution;
[0045] (2) The mixed solution is mixed with α, β-sodium glycerophosphate for physical cross-linking, and then genipin is added for chemical cross-linking to obtain a thermosensitive hydrogel dressing loaded with trypsin antibacterial biofilm.
[0046] In the present invention, the preparation method of the quaternary ammonium salt chitosan is: mixing the chitosan solution with the 2,3-epoxypropyltrimethylammonium chloride solution for reaction for 20 to 28 hours, adjusting the pH to 6.8 to 7.2, and obtaining the quaternary ammonium salt chitosan after suspension evaporation and freeze-drying; preferably reacting for 21 to 27 hours; more preferably reacting for 22 to 26 hours; more preferably reacting for 24 hours.
[0047] In the present invention, the adjusted pH is preferably 6.9 to 7.1, and more preferably 7.0.
[0048] In the present invention, the mass percentage concentration of the chitosan solution is 1.5-2.5%; preferably 1.7-2.3%; more preferably 1.9-2.1%; and more preferably 2%.
[0049] In the present invention, the chitosan solution uses an alkali-urea aqueous solution as solvent.
[0050] In the present invention, the concentration of potassium hydroxide in the alkali-urea aqueous solution is 14-18 g / 100 mL; the concentration of urea is 6-10 g / 100 mL; preferably, the concentration of potassium hydroxide is 15-17 g / 100 mL; the concentration of urea is 7-9 g / 100 mL; more preferably, the concentration of potassium hydroxide is 16 g / 100 mL; the concentration of urea is 8 g / 100 mL.
[0051] In the present invention, the volume ratio of the chitosan solution to the 2,3-epoxypropyltrimethylammonium chloride solution is 1:0.8-1.2; preferably 1:0.9-1.1; more preferably 1:1.
[0052] In the present invention, the mass ratio of the quaternary ammonium salt chitosan to trypsin is 3 to 5:1, preferably 4:1.
[0053] In the present invention, the mass ratio of the mixed solution to α, β-sodium glycerophosphate and quaternary ammonium salt chitosan is 7:20-32; preferably 7:22-30; more preferably 7:24-28; more preferably 7:26.
[0054] In the present invention, the mass ratio of genipin to quaternary ammonium salt chitosan is 0.01-0.03:7, preferably 0.02:7.
[0055] In the present invention, the physical crosslinking time is 3 to 5 minutes, and the temperature is 35 to 40°C; preferably, the physical crosslinking time is 3 to 5 minutes, and the temperature is 37°C; more preferably, the physical crosslinking time is 3 minutes, and the temperature is 37°C.
[0056] In the present invention, the chemical cross-linking time is 3 to 24 hours, and the temperature is 3 to 40°C; preferably, the chemical cross-linking time is 3 to 24 hours, and the temperature is 35 to 40°C; further preferably, the chemical cross-linking time is 3 to 12 hours, and the temperature is 35 to 40°C; more preferably, the chemical cross-linking time is 3 hours, and the temperature is 37°C.
[0057] The invention also provides a temperature-sensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, which is prepared by the preparation method.
[0058] The present invention also provides the use of the thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm in the preparation of a product promoting wound repair.
[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0060] Example 1
[0061] A method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, comprising the following steps:
[0062] (1) Disperse 1.5 g of purified chitosan powder in 98 g of an alkali-urea aqueous solution and stir for 2 h at -25°C to prepare a 2% chitosan solution; the concentration of potassium hydroxide in the alkali-urea aqueous solution is 14 g / 100 mL, and the concentration of urea is 6 g / 100 mL.
[0063] (2) centrifuging the chitosan solution at 4°C, 7000 rpm for 5 min to remove impurities;
[0064] (3) dissolving 11.5 g of 2,3-epoxypropyltrimethylammonium chloride in 89 mL of deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution;
[0065] (4) At 0°C, 2,3-epoxypropyltrimethylammonium chloride solution was slowly added to the chitosan solution (volume ratio of 0.8:1), stirred for 20 h, and centrifuged at 7000 rpm for 5 min to remove impurities;
[0066] (5) The reaction solution was adjusted to pH 6.8 with HCl, and quaternary ammonium salt chitosan was obtained after suspension evaporation and freeze-drying.
[0067] (6) mixing the obtained quaternary ammonium salt chitosan and trypsin in a mass ratio of 3:1 to obtain a mixed solution;
[0068] (7) mixing the mixed solution with α, β-sodium glycerophosphate in a mass ratio of 7:20 and stirring for physical crosslinking; the physical crosslinking time is 4 minutes and the temperature is 37° C.;
[0069] (8) Genipin is added to the mixed solution and stirred for chemical cross-linking to obtain a thermosensitive hydrogel dressing (T-QGG) loaded with trypsin antibacterial biofilm; the mass ratio of the genipin to the quaternary ammonium salt chitosan is 0.01:7; the time of the chemical cross-linking is 5 hours and the temperature is 37°C.
[0070] Example 2
[0071] A method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, comprising the following steps:
[0072] (1) Disperse 2.5 g of purified chitosan powder in 98 g of an alkali-urea aqueous solution and stir for 2 h at -25°C to prepare a 2% chitosan solution; the concentration of potassium hydroxide in the alkali-urea aqueous solution is 18 g / 100 mL, and the concentration of urea is 10 g / 100 mL.
[0073] (2) centrifuging the chitosan solution at 4°C, 9000 rpm for 9 min to remove impurities;
[0074] (3) dissolving 10.5 g of 2,3-epoxypropyltrimethylammonium chloride in 89 mL of deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution;
[0075] (4) At 0°C, 2,3-epoxypropyltrimethylammonium chloride solution was slowly added to the chitosan solution (volume ratio of 1.2:1), stirred for 28 h, and centrifuged at 9000 rpm for 9 min to remove impurities;
[0076] (5) The reaction solution was adjusted to pH 7.2 with HCl, and quaternary ammonium salt chitosan was obtained after suspension evaporation and freeze-drying.
[0077] (6) mixing the obtained quaternary ammonium salt chitosan and trypsin in a mass ratio of 5:1 to obtain a mixed solution;
[0078] (7) mixing the mixed solution with α, β-sodium glycerophosphate in a mass ratio of 7:32 and stirring for physical crosslinking; the physical crosslinking time is 3 minutes and the temperature is 37° C.;
[0079] (8) Genipin is added to the mixed solution and stirred for chemical cross-linking to obtain a thermosensitive hydrogel dressing loaded with trypsin antibacterial biofilm; the mass ratio of the Genipin to the quaternary ammonium salt chitosan is 0.03:7; the time of the chemical cross-linking is 3 hours and the temperature is 37°C.
[0080] Example 3
[0081] A method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, comprising the following steps:
[0082] (1) Disperse 2 g of purified chitosan powder in 98 g of an alkali-urea aqueous solution and stir for 2 h at -25°C to prepare a 2% chitosan solution; the concentration of potassium hydroxide in the alkali-urea aqueous solution is 16 g / 100 mL, and the concentration of urea is 8 g / 100 mL.
[0083] (2) centrifuging the chitosan solution at 4°C, 8000 rpm for 7 min to remove impurities;
[0084] (3) dissolving 11 g of 2,3-epoxypropyltrimethylammonium chloride in 89 mL of deionized water to obtain a 2,3-epoxypropyltrimethylammonium chloride solution;
[0085] (4) At 0°C, 2,3-epoxypropyltrimethylammonium chloride solution was slowly added to the chitosan solution (volume ratio was 1:1), stirred for 24 h, and centrifuged at 8000 rpm for 7 min to remove impurities;
[0086] (5) The reaction solution is adjusted to pH 7 with HCl, and then suspended and evaporated and freeze-dried to obtain quaternary ammonium salt chitosan.
[0087] (6) mixing the obtained quaternary ammonium salt chitosan and trypsin in a mass ratio of 4:1 to obtain a mixed solution;
[0088] (7) mixing the mixed solution with α, β-sodium glycerophosphate in a mass ratio of 7:28 for physical crosslinking; the physical crosslinking time is 4 minutes and the temperature is 37° C.;
[0089] (8) Genipin is added to the mixed solution and stirred for chemical cross-linking to obtain a thermosensitive hydrogel dressing loaded with trypsin antibacterial biofilm; the mass ratio of the Genipin to the quaternary ammonium salt chitosan is 0.02:7; the time of the chemical cross-linking is 4 hours and the temperature is 37°C.
[0090] Experimental Example 1
[0091] Application of the present invention in diabetic wounds accompanied by mixed bacterial biofilm formation
[0092] In order to verify the effect of thermosensitive quaternary ammonium chitosan hydrogel on diabetic wounds with mixed bacterial biofilm formation, the thermosensitive quaternary ammonium chitosan hydrogel prepared in Example 1 was selected, and SD rats were used as experimental animals to establish a diabetic wound model with mixed bacterial biofilm formation ( Figure 7 ).
[0093] 1. Characterization of Thermosensitive Quaternary Ammonium Salt Chitosan Hydrogel
[0094] (1) Fresh thermosensitive quaternary ammonium salt chitosan hydrogel was prepared. The storage modulus (G') and loss modulus (G") of the thermosensitive quaternary ammonium salt chitosan hydrogel were measured by a rheometer (MCR 92, Anton Paar, Australia) when the temperature increased from 5°C to 40°C at a rate of 1°C per minute. The gel point (G) of the QGG hydrogel was determined. Figure 2 ).
[0095] After pre-gelling in a rectangular container at 37°C for 10 min, the samples were cut into 1×1×7 cm 3 3 equal parts and 3×3×2cm 3 The tensile strength of the hydrogel was measured using a 50KN electronic universal testing machine (CMT6103 / ZWICK / Instron 5969, Instron, USA). Figure 3 ).
[0096] (2) Prepare a thermosensitive quaternary ammonium salt chitosan hydrogel loaded with trypsin according to the steps of Example 1 above, and place it at 37°C for 10 minutes to form a hydrogel. 3 The hydrogels of different sizes were placed in 50 mL of PBS solution. To maintain the activity of trypsin, the system was kept at 4°C and magnetically stirred.
[0097] Take 3 mL of soaking solution at 0 h, 0.5 h, 1 h, 2 h, 4 h, 7 h, 12 h, 24 h, 48 h, 64 h and 72 h, and add 3 mL of fresh PBS solution, with 3 replicates in each group. Use a trypsin kit to measure the trypsin concentration of the soaking solution at different time points. The experimental steps are as follows:
[0098] First, adjust the wavelength of the UV spectrophotometer to 253 nm and use a quartz cuvette filled with double distilled water to zero the machine; then, prepare the trypsin substrate application solution, which must be used promptly after preparation: add the powder in the kit to the diluent, and after fully dissolving, let it stand in a 37°C water bath for 5 minutes.
[0099] Take the EP tube and mark it, add 1.5mL of sample (i.e., the soaking solution collected at different time points) and 1.5mL of trypsin substrate application solution, shake well, transfer the mixture to a quartz cuvette, and measure the absorbance A1 of the mixture at 253nm. Subsequently, pour the mixture back into the EP tube, place it in a 37℃ water bath and let it stand for 20min, and then measure the absorbance A2 of the mixture at 253nm again. The trypsin concentration in the soaking solution at different time points can be obtained by the following trypsin activity calculation formula ( Figure 4 ).
[0100] The formula for calculating trypsin activity is as follows:
[0101] Trypsin (U / mg prot) = (ΔA 测定 -ΔA 空白 ) / 0.003*V 反总 / V 样品 *1 / V 样品 / T
[0102] Wherein, ΔA determination = A2-A1; ΔA blank: measured using reagent 2 in the kit in the same method as the sample; V total = V sample + V trypsin substrate application solution; T: reaction time (i.e. 20 min).
[0103] 2. Application of thermosensitive quaternary ammonium salt chitosan hydrogel
[0104] (1) The bacterial concentrations of Staphylococcus aureus, Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus, and multidurable Pseudomonas aeruginosa were adjusted to 10 6 CFU / mL. Select the 4 rows × 8 columns of the well plate in the center of the 96-well plate, add 150 μL of bacterial suspension to each well, and re-shock and shake the bacterial suspension after each continuous drop of a row to prevent the sedimentation of bacteria from causing differences in the concentration of bacteria added to each well. Add 200 μL of PBS solution to the outermost wells around the 96-well plate to prevent the culture solution from evaporating. Place the 96-well microtiter plate in a 37°C constant temperature bacterial incubator and culture it for 60 hours to obtain a mature bacterial biofilm.
[0105] Gently use a pipette to remove the liquid culture medium in the 96-well plate, and rinse it once with PBS solution to remove planktonic bacteria, avoiding contact with the wall and bottom of the well plate to avoid damaging the bacterial biofilm. Then, add 150 μL of PBS solution, levofloxacin solution or penicillin G solution, QCS (prepared in Example 1) solution and trypsin solution to the well plate, respectively, with 5 replicates per group. In a 37°C constant temperature bacterial incubator, the bacterial biofilm was incubated with the reagent for 1 to 12 hours, and then crystal violet staining was performed for quantification, as follows:
[0106] Add 200 μL of methanol to the well plate and incubate at room temperature for 20 minutes to fix the bacteria. After removing the methanol, add 200 μL of 1% crystal violet solution to the well plate and incubate at room temperature for 15 minutes. At the same time, methanol and crystal violet should be added to the blank well plate in sequence as a blank control. After removing the crystal violet solution, wash the well plate three times with PBS solution, and place the 96-well plate in a 37°C constant temperature bacterial incubator to dry. Subsequently, add 200 μL of 30% glacial acetic acid solution to the well plate, and incubate at room temperature for 20 minutes to allow the glacial acetic acid to fully dissolve the crystal violet-stained bacterial biofilm. Finally, read the absorbance of the crystal violet-stained bacterial biofilm in the 96-well plate at a wavelength of 550 nm ( Figure 5 , Figure 6 ), record and analyze.
[0107] (2) 60 healthy SD rats (male, about 300 g, 6-8 weeks old) were purchased from Beijing Weitong Lihua Experimental Animal Technology Co., Ltd. After passing the quarantine, they were placed in the laboratory of Wuhan University Animal Experiment Center (SPF grade) for adaptive feeding for 1 week. This animal experiment has passed the experimental animal welfare ethics review of Wuhan University Zhongnan Hospital.
[0108] STZ (streptozotocin) is unstable in nature and needs to be dissolved in 0.1mmol / L citric acid / sodium citrate buffer at 0℃. Prepare it now and use it now. The preparation method of 0.1mmol / L citric acid / sodium citrate buffer is as follows: dissolve 2.1g of citric acid in 100mL of double distilled water, recorded as liquid A; dissolve 2.94g of trisodium citrate in 100mL of double distilled water, recorded as liquid B. Precool liquid A, liquid B and 100mL of double distilled water in crushed ice for later use. Perform the following operation on an ice box: take 14mL of liquid A, 11mL of liquid B and 25mL of double distilled water and mix them evenly. Measure the pH value in the range of 4.25 to 4.50 to obtain 0.1mmol / L citric acid / sodium citrate buffer.
[0109] The rats were weighed and blood glucose was tested by sampling blood from the rat tail vein one day before STZ injection. After fasting and depriving the rats of water for 16 hours, STZ (65 mg / kg) was injected into the rats by intraperitoneal injection. The whole process should be performed aseptically. The rats resumed eating and drinking 30 minutes after STZ injection. The rats were closely monitored, and feed and drinking water were replenished and bedding was replaced in time.
[0110] 72 hours after STZ injection, blood was collected again through the rat tail vein, blood sugar was measured, and body weight was measured at the same time. If the rat blood sugar was still within the normal range, STZ (30 mg / kg) could be injected intraperitoneally. If the rat blood sugar was higher than the normal range, the rat tail blood sugar was randomly measured 3 times in the next week, and the rat body weight was recorded. If the rat blood sugar was above 11.1 mmol / L, and there was polyphagia, polydipsia, and polyuria, it indicated that the diabetic rat model was successfully established.
[0111] Polyurethane film was used to culture a mature bacterial biofilm of mixed Staphylococcus aureus, Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus in vitro for later use. Selected successfully induced diabetic rats, the rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital at a dose of 50 mg / kg. The rats were fixed on the operating table in a prone position, and the hair on the back of the rats was removed with a shaver to fully expose the back skin of the rats. A full-thickness skin defect was made on both sides of the rat spine with a circular punch with a diameter of 1.5 cm. Note that the punch must be perpendicular to the skin, and the wound edges were trimmed with surgical scissors.
[0112] Place the ruler parallel to the edge of the wound and take a photo to record the size of the wound. Next, stick the polyurethane film with bacterial biofilm to the wound, making sure that the side with bacterial biofilm is close to the wound. Then, fix it with 3M sterile film and bandage it again with gauze. After the rat wakes up, put it back into the cage, give it normal feed, drinking water, change the bedding, and closely observe the general condition of the rat.
[0113] About 2 days later, a large number of yellow-white (or green) purulent scabs can be observed on the wounds of diabetic rats. The wounds of four groups of diabetic rats with bacterial biofilm formation were changed according to the clinical dressing operation, as follows: the rats were anesthetized by inhalation of ether. The gauze was removed, a ruler was placed parallel to the wound, and the general condition of the wound was recorded by taking pictures. Then, the purulent substances on the surface of the wound were wiped from the uninfected area to the infected area with iodine cotton balls, and repeated three times. According to the grouping, different wound dressings were used for the wounds of diabetic rats with bacterial biofilm formation. To prevent the rats from moving or biting each other, the outer layer of the dressing was fixed with an elastic bandage again. After the rats woke up, they were put back into the feeding cage for continued feeding, and the general condition of the rats was closely observed and the bedding was replaced in time.
[0114] The wound modeling time was recorded as -2 days, and photos were taken against the scale at -2 days, 0 days (i.e., the time when the dressing was first used), and 3 days, 7 days, 10 days, and 14 days to record the healing of the rat wound area. At the same time, according to the grouping, the dressing operation was performed on the diabetic wound with bacterial biofilm formation ( Figure 8 , Fig. 9 ).
[0115] (3) α-SMA (α-Smoothmuscle actin) and CD 31 are highly expressed in vascular smooth muscle cells and vascular endothelial cells. Immunohistochemical staining of α-SMA and CD 31 can show the regeneration of microvessels in the wound surface. Therefore, the present invention selects to slice the wound surface and the full-thickness cross-section of normal skin to visually show the proliferation of blood vessels in the wound surface. The wax block of the wound tissue on the 7th day was selected for slicing, dewaxing, and alcohol-immersion in water. Immunohistochemical preparation was then performed, and the specific operation was as follows:
[0116] The sample was completely immersed in citrate buffer (pH = 6.0), heated in a microwave oven at medium heat for 5 minutes, cooled to room temperature, and rinsed with distilled water 3 times, 5 minutes each time. 50 μL of 0.2% TritonX-100 was added to the sample, and the membrane was broken after standing for 30 minutes, and then rinsed with distilled water 3 times. At room temperature, 5-10% goat serum was used to block for 10 minutes, and the serum was removed, and the primary antibody working solution was added, and incubated at 4°C overnight. After rewarming at room temperature, it was rinsed with distilled water 3 times, and the water was dried, and the secondary antibody was added, incubated at 37°C for 15 minutes, and rinsed with distilled water 3 times. Then, an appropriate amount of DAB solution was added, and the staining was stopped under a microscope until the staining was appropriate, and the staining was stopped and rinsed with distilled water. After the slice was immersed in Weigert's iron hematoxylin solution for 3-5 minutes, it was rinsed with distilled water. Differentiation was performed with 1% hydrochloric acid alcohol (about 3s), and then rinsed with distilled water again. Finally, the above experimental steps were followed again for dehydration and transparency treatment, and then the slides were sealed with neutral gum, observed under a microscope, and images were collected ( Fig.10 ).
[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm, characterized in that: The steps include: (1) mixing quaternary ammonium salt chitosan and trypsin to obtain a mixed solution; (2) The mixed solution is mixed with α, β-sodium glycerophosphate for physical cross-linking, and then genipin is added for chemical cross-linking to obtain a thermosensitive hydrogel dressing loaded with trypsin antibacterial biofilm.
2. The preparation method according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt chitosan comprises: mixing a chitosan solution with a 2,3-epoxypropyltrimethylammonium chloride solution for reaction for 20 to 28 hours, adjusting the pH value to 6.8 to 7.2, and obtaining the quaternary ammonium salt chitosan after suspension evaporation and freeze drying.
3. The preparation method according to claim 1, characterized in that: The mass percentage concentration of the chitosan solution is 1.5-2.5%; the mass percentage concentration of the 2,3-epoxypropyltrimethylammonium chloride solution is 9-13%; and the chitosan solution uses an alkali-urea aqueous solution as a solvent.
4. The preparation method according to claim 3, characterized in that: The concentration of potassium hydroxide in the alkali-urea aqueous solution is 14-18 g / 100 mL, and the concentration of urea is 6-10 g / 100 mL.
5. The preparation method according to claim 1, characterized in that: The volume ratio of the chitosan solution to the 2,3-epoxypropyltrimethylammonium chloride solution is 1:0.8-1.
2.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the quaternary ammonium salt chitosan to trypsin is 3-5:
1.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the mixed solution to α, β-sodium glycerophosphate and quaternary ammonium salt chitosan is 7:20-32; the mass ratio of genipin to quaternary ammonium salt chitosan is 0.01-0.03:
7.
8. The preparation method according to claim 1, characterized in that: The physical cross-linking time is 3 to 5 minutes, and the temperature is 35 to 40°C; the chemical cross-linking time is 3 to 24 hours, and the temperature is 4 to 37°C.
9. The thermosensitive hydrogel dressing loaded with trypsin to resist bacterial biofilm prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the trypsin-loaded antibacterial biofilm-resistant thermosensitive hydrogel dressing according to claim 9 in the preparation of a product for promoting wound repair.
Citation Information
Patent Citations
Injectable chitosan composite hydrogel capable of promoting myocardium repair and preparation method of injectable chitosan composite hydrogel
CN104922734A
Homogeneous synthesis method for quaternary ammonium salt chitosan
CN110386994A
Preparation method of temperature-sensitive gel type medical dressing based on fabric
CN114306716A
Protease formulations for treatment of microbial infections
CN115666512A
Antibacterial, antioxidant and self-adhesive multifunctional composite hydrogel dressing and preparation method thereof
CN116350840A